KORELASI LAMA MENDERITA SAKIT TERHADAP TINGKAT STRES PENDERITA HIPERTENSI - Juwita, Linda; Agustinah, Rika Budi (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2019)
Hypertension (HT) requires prolonged treatment, inducing personal worries and fear resulted instress. This study aimed to analyze the correlation between HT duration and stress levels in adults.This cross-sectional study involved 38 adults with HT in the working area of Kedungdoro PublicHealth Center, Surabaya. Purposive sampling was implemented and sample size of 38 obtained.Valid and reliable instrument was used in data collection. Spearman Rank correlation test was usedin data analysis. Results showed that the majority of respondents were female, 41-60 years old,uneducated, married, housewives, and regularly consume HT medication. Most of them had HT lessthan one year, and reported moderate level of stress. There was no significant correlation betweenHT duration and stress level in adults (p = .541). Adaptive coping applied could result in positiveadaptations or adjustment.